Fleksibelitas Hukum Ekonomi Syariah - Ridwan, Murtadho (TAWAZUN: Journal of Sharia Economic Law, 2018)
This study aims to examine the flexibility of Islamic law in general and the flexibility of Islamic law in particular. This study is a literature review. Data is collected from various works that have been produced by the scholars and analyzed descriptively. The results of the study show that in general, Islamic law is divided into two types; First, Islamic law is static (fixed) and will not change, this type of law is based on Nash qath'i. Second, Islamic law that is flexible (dynamic) that can change according to the demands of the times, this type of law is based on the results of ijtihad. Many flexible laws are found in the law of muamalat (Islamic economics) and this has happened since the beginning of Islam. There are many examples of the flexibility of Islamic economic law, including: Umar stopped distributing the land from the war, even though the Messenger of Allah had distributed the land; Umar stopped the portion of the zakat property for the convert group even though they belonged to eight groups who were entitled to receive zakat shares; Umar made a policy to excise non-Muslim traders as big as Usyur (10%) and Dzimmah Expert traders by 5% when they entered the Islamic region; and Umar founded the Diwan (Baitul Mal) even though it never existed at the time of the Prophet.